ANALISIS PENGARUH SIZE, LEVERAGE, DAN PROFITABILITAS TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN PROPERTY DAN REALESTATE YANG TERDAFTAR DI BEI (Periode 2010-2013) - B31110062, Sutarto (Jurnal Manajemen Update, 2015)
One ratio that is widely used in making investment decisions are PER (Price EarningsRatio). This ratio is used to evaluate the position, performance and financial condition of thecompany in making investment decisions. Price Earning Ratio (PER) comparing the stockprice (which is derived from the capital market) and earnings per share are obtained by theowner of the company are presented in the financial statements, Husnan and Pudjiastuti,(2006:75) Investors may consider this ratio in order to sort out which shares will be able toprovide great benefits in the future.Â This study aims to determine whether the ratio of Size, Leverage and Profitabilityaffect the Price Earning Ratio (PER) in the Property and Realestate companies listed inIndonesia Stock Exchange. This study used a sample of 19 Property and Realestatecompanies listed on the Stock Exchange in the period 2010-2013. Tests using descriptivestatistics and multiple regression analysis. Results showed Size significant and positiveimpact on the Price Earning Ratio, Profitability significant but have a negative relationship toPrice Earning Ratio. leverage effect negative and insignificant impact Price Earning Ratio.Keywords: Size, Leverage, Profitability, Price Earning Ratio,